2012
DOI: 10.1093/fampra/cms007
|View full text |Cite
|
Sign up to set email alerts
|

Excising squamous cell carcinomas: comparing the performance of GPs, hospital skin specialists and other hospital specialists

Abstract: GPs excise a considerable number of SCCs in primary care. GPs compare favourably to skin specialists in excising SCCs. The performance of infrequent GP excisers does not appear to differ significantly from that of frequent GP excisers. Further work is required to define more clearly the role of GPs in the management of SCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 12 publications
4
30
0
Order By: Relevance
“…We previously demonstrated that GP excision rate of skin cancer in three Scottish Health Boards was lower (76.9%) compared with those of secondary care dermatology (94.1%) and plastic surgery (89.3%), which concurs with other studies from Scotland and the Netherlands . However, other studies have reported that GPs excise NMSC as well as skin specialists . There is limited evidence assessing specifically whether GPs with a degree of skin surgery specialism or frequency of practice have superior excision performance.…”
supporting
confidence: 81%
“…We previously demonstrated that GP excision rate of skin cancer in three Scottish Health Boards was lower (76.9%) compared with those of secondary care dermatology (94.1%) and plastic surgery (89.3%), which concurs with other studies from Scotland and the Netherlands . However, other studies have reported that GPs excise NMSC as well as skin specialists . There is limited evidence assessing specifically whether GPs with a degree of skin surgery specialism or frequency of practice have superior excision performance.…”
supporting
confidence: 81%
“…Delaney et al [10] also noted that most histopathology forms of GPs and hospital specialists did not include a presumptive diagnosis. It may be concluded that many physicians are not aware of the fact that a diagnosis/consideration on the histopathology form may be of help for the pathologist in establishing the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, the same authors found that GPs performed as well, if not better, than specialists in excising squamous cell carcinomas (SCC); whereas, again, practicebased GPs performed as well as GPwSIs. 3 Further research by the same authors showed that melanoma excisions by GPs appeared to be of similar quality to those undertaken by specialists; there was no difference demonstrated between frequent and infrequent GP surgeons. 4 This article describes how GP minor surgery is taking place and they are removing pigmented lesions, despite national guidance that they should be referred to secondary care as GPs perform less well.…”
Section: Introductionmentioning
confidence: 93%